2001
DOI: 10.1073/pnas.161098098
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genomics of Staphylococcus aureus : Insights into the origin of methicillin-resistant strains and the toxic shock syndrome epidemic

Abstract: An emerging theme in medical microbiology is that extensive variation exists in gene content among strains of many pathogenic bacterial species. However, this topic has not been investigated on a genome scale with strains recovered from patients with welldefined clinical conditions. Staphylococcus aureus is a major human pathogen and also causes economically important infections in cows and sheep. A DNA microarray representing >90% of the S. aureus genome was used to characterize genomic diversity, evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
261
3
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(287 citation statements)
references
References 17 publications
(11 reference statements)
15
261
3
4
Order By: Relevance
“…Previous studies have demonstrated that the majority of cases of menstrual TSS are caused by a single clone that corresponds to CC30 (33,34). However, the distribution of the tst gene encoding the toxic shock syndrome toxin 1 (TSST-1) among CC30 subclades has not been previously examined.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the majority of cases of menstrual TSS are caused by a single clone that corresponds to CC30 (33,34). However, the distribution of the tst gene encoding the toxic shock syndrome toxin 1 (TSST-1) among CC30 subclades has not been previously examined.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative genomic hybridization (CGH) is a powerful genetic tool for the study of bacteria (Dobrindt et al, 2003;Fitzgerald et al, 2001Fitzgerald et al, , 2003Fukiya et al, 2004;Israel et al, 2001;Leavis et al, 2007;Lindsay et al, 2006;Paauw et al, 2008;Porwollik et al, 2002;Salama et al, 2000). Most CGH arrays have been designed from annotated wholegenome sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The whole genome sequencing of seven S. aureus strains (N315 [19], Mu50 [19] (11) demonstrated that 2,198 (78%) of the 2,817 COL chromosomal open reading frames (ORFs) represented on a DNA microarray were shared by the 36 analyzed S. aureus isolates from various sources, which belonged to 14 multilocus enzyme electrophoretic types. Ten of the 18 large regions of difference carry genes that encode putative virulence factors and proteins that mediate antibiotic resistance.…”
mentioning
confidence: 99%